Anterior fontanelle size among term neonates on the first day of life born at University of Gondar Hospital, Northwest Ethiopia - Oumer, Mohammed (PLoS One, 2018)
BACKGROUND: Anterior fontanelle is the largest, prominent and most important fontanelle, which is used for clinical evaluation. It is mainly characterized by its size and shape variation and is possibly influenced by gender, race and genetics. Understanding the variation of anterior fontanelle is used for recognition of different medical disorders and abnormal skeletal morphogenesis. OBJECTIVE: To determine the mean size of anterior fontanelle among term neonates on the first day of life born at University of Gondar Hospital, Gondar Town, Northwest Ethiopia, 2018. METHODS: Descriptive cross sectional study design was undertaken in 384 term and apparently healthy neonates, using standard methods. Descriptive analysis, student t-test, one way ANOVA and Pearson correlation coefficient were implemented. RESULTS: In this study, the mean size of anterior fontanelle in term neonates was 3.00 ± 0.62 cm (range 1.70–5.50 cm). The mean size of anterior fontanelle was 3.10 ± 0.66 cm for males, and 2.88 ± 0.57 cm for females. There was statistically significant difference in anterior fontanelle size in neonates of different genders (p<0.001), mode of delivery (p<0.001) and duration of labour (p = 0.006). However, the size of anterior fontanelle was not significantly affected by the birth order, onset of labour and socio-demographic variables of the mother except occupation of the mother (p = 0.01). There was a significant positive correlation between the mean size of anterior fontanelle with birth weight (r = 0.11; p = 0.04) and head circumference (r = 0.17; p = 0.001). CONCLUSIONS: At term, male neonates had significantly larger anterior fontanelle than female neonates and anterior fontanelle size has a direct relationship with birth weight and head circumference.